Making Better Decisions by Thinking in Bets. - Mockaitis | How to Be Awesome at Your Job, Pete (linkedin.com, 2020)
Learn to make better, more informed decisions in an unpredictable world in this course adapted from the podcast How to Be Awesome at Your Job.